Simplified laparoscopic sacropexy avoiding deep vaginal dissection. Issue 2 (24th August 2018) - Cosma, Stefano; Petruzzelli, Paolo; Chiadò Fiorio Tin, Michela; Parisi, Silvia; Olearo, Elena; Fassio, Federica; Zizzo, Roberto; Danese, Saverio; Benedetto, Chiara
Abstract: Objective: To evaluate the safety and efficacy of a "simplified " laparoscopic sacropexy approach. Methods: Data were retrospectively assessed from women with apical prolapse of stage 2 or higher who underwent "simplified" laparoscopic sacropexy between October 1, 2010, and May 31, 2017 at the St Anna Hospital, City of Health and Science, Torino, Italy. Patients were treated with the "simplified" laparoscopic sacropexy, where meshes were anchored solely to the vaginal apex, even in the presence of advanced multi‐compartment vaginal prolapse. Data on prolapse stage and urogenital functions collected through clinical examinations, and questionnaires at baseline, 6 months, 12 months, and annually thereafter were examined. Results: Overall, 121 women were included in the analysis; the mean follow‐up was 33.2 months. Mean operative time was 135.1 minutes; there were no intraoperative visceral or vascular injuries. There was 1 (0.8%) patient who experienced recurrence, and 2 (1.7%) who experienced vaginal erosion. Both urogenital symptom scores (all P <0.05) and quality of life scores (all P <0.05) improved significantly. Conclusion: Adequate re‐suspension of only the apex was sufficient to correct other vaginal compartments, even for women with preoperative multi‐compartment prolapse higher than POP‐Q stage 2. The "simplified" laparoscopic sacropexy was an efficacious intraoperative time‐saving technique; it could reduce adverse events caused by deep vaginal dissection up to puborectal muscles and the bladder trigone. Abstract : Adequate re‐suspension of the vaginal apex could satisfactorily correct all vaginal compartments, even in the presence of advanced prolapse.